Strategi Lobi dan Negosiasi Awardee BSI Scholarship Inspirasi UNJ Dalam Menjalin Kerjasama Pada Program SIBERKASIH di Kampung Pure Bali Rawamangun - Nerissa Mutiara Murpratiwi; Intan Maharani Putri; Patricia Mora Manarung; Dini Safitri (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Lobbying and negotiation are the strategic aspects used to construct reassurance and agreement on a common goal. Therefore, it is aligned with the collaboration context carried out by the UNJ BSI Scholarship Inspiration Awardee in creating a SIBERKASIH program with the residents of Kampung Pure Bali Rawamangun. BSI Scholarship Inspiration UNJ is an association of Jakarta State University students who received scholarship from the BSI Scholarship Inspiration program under Bank Syariah Indonesia and BSI Maslahat. SIBERKASIH (Smart, Inspirasi, Penuh kasih) was created to offer free English Language course using fun-learning method to develop the children's English knowledge and skills. This research used a descriptive qualitative approach using interview to collect the accurate data stated by particular people who performed the lobbying and negotiation technique. This study found that there are several lobbying and negotiation strategies that took place in the cooperation. Those are direct lobbying strategy and the negotiation strategy that prioritizes the benefits of both parties.